Systematic Literature Review of Cloud Computing Adoption - Perdly Setiawan; Raihan Shidqi Putrandi; Imelda Imelda (INOVTEK Polbeng - Seri Informatika, 2024)
In the current rapidly growing digital era, cloud computing is a technology that plays a significant role in digital transformation in various industrial sectors. Cloud computing brings several advantages such as high scalability, cost efficiency, flexibility, easy accessibility, collaboration enhancement, more effective data backup and recovery, and automatic software updates. However, the adoption process faces numerous challenges and complex considerations, such as data security, privacy, regulatory compliance, and integration with existing systems. This research employed a systematic literature review (SLR) method to collect, analyze, and synthesize various studies on cloud computing adoption. The results are expected to provide comprehensive guidance for practitioners and researchers in understanding the dynamics of cloud computing adoption, as well as recommendations for organizations to establish more informative and strategic decisions in implementing this technology to improve their competitiveness and operational efficiency.